Religiosity, Poverty, Health, and Education Effects on Islamic Human Development through Economic Growth in West Java - Dede Nurwahidah; Mustofa Mustofa; Moh. Najib; Mohamad Anton Athoillah (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This article analyzes the effects of religiosity, poverty, health, and education on the Islamic Human Development Index (I-HDI) in West Java during 2020-2024, with economic growth positioned as an intervening variable. Method: Using a quantitative descriptive-verificative design, the study employs secondary panel data from 21 regencies/cities over five years, resulting in 105 observations. Fixed Effect Model regression, path analysis, and the Sobel test were processed with EViews 10. Results: Religiosity and poverty have negative significant effects on I-HDI, with coefficients of -0.3421 (p=0.0002) and -0.5123 (p=0.0000). Health, education, and economic growth have positive significant effects, with coefficients of 0.6789, 0.3891, and 0.4123. Economic growth partially mediates health and education but does not mediate religiosity and poverty. The model explains 81.23 percent of I-HDI variation. Conclusion: West Java recovered economically, but maqasid-based human development remained low. In 2024, I-HDI reached 52.72, below conventional HDI of 74.92, indicating the need for moral-security strengthening, spatial poverty reduction, health protection, and education reform.